Impact of Nutrient Management Practices on the Status and Quality of Soil Humus in Newly Developed Terraced Land - Dutta, Manoj; Chauhan, B. S. (International Journal of Bio-resource and Stress Management, 2023)
An experiment was conducted in the experimental farm at School of Agricultural Sciences and Rural Development, Medziphema, Nagaland to evaluate the impact of different nutrient management practices on content and quality of soil humus in a newly developed terraced land. Twelve treatments involving N, P and K (NPK) fertilizers, farmyard manure (FYM), poultry litter, forest litter, Azospirillum and Zn either alone or in combinations were applied continuously for two years. On an average, fulvic C, humic C and humin C was 48.1, 21.1 and 30.8% of humus C, respectively. The fulvic C was the largest fraction of humus C in soil followed by humin C and humic C. With the present rate of accumulation of humus C, the soil under different treatments showing build up of humus C would take 3.5 to 66.0 years with an average of 23.2 years to reach its original C content present before terracing. Among the fractions, fulvic N was the largest fraction of humus N in all the treatments followed by humic N or humin N. On an average, fulvic N, humic N and humin N was 58.8, 21.2 and 20.0% of humus N, respectively. After two years, the rate of build up of humus N in various nutrient management practices was 18.3 to 76.4 kg N ha-1 yr-1 with an average of 44.5 kg N ha-1 yr-1. Among the fractions, fulvic P was the largest fraction of the humus P followed by humic P and humin P in all the treatments. On an average, fulvic P, humic P and humin P constituted 65.4, 20.5 and 14.1% of humus P, respectively. The lowest C:N:P ratio of soil humus, fulvic acid and humic acid was in NPK+Poultry litter treatment. The average C:N:P ratios of soil humus, fulvic acid, humic acid and humin was estimated to be 133.1:10.8:1, 98.2:9.8:1, 138.0:11.4:1 and 281.8:15.0:1, respectively.